PRODUKSI PROTEIN SEL TUNGGAL DARI KULTUR Rhizopus oryzae DENGAN MEDIUM LIMBAH CAIR TAHU - Leny Maryana; Syariful Anam; Arsa Wahyu Nugrahani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
Tofu wastewater is the origination of tofu’s production process that can degrade the quality of the environment if not handled properly. Another impact of this waste is the potential attack that could evoke the diseases such as diarrhea, skin diseases, and other illnesses for people who use the stream flow that has been polluted by this wastewater. However, the high-carbohydrate and protein of this waste may allow it to be used more as a microbial growth substrate to produce a Single-cell Protein. The purpose of this study is to determine the optimum incubation time and the highest protein content of Rhizopus oryzae in the medium of tofu wastewater based on the calculation of protein content percentage and the analysis of cell dry mass. And to know the optimum pH growth with the variation of pH growth which is about 4, 5, and 6. The calculation is performed in accordance with the fermentation time at 24, 48, and 72 hours. Total protein content calculated by the Kjeldahl method. The results showed the highest protein content obtained in the incubation period to 48 hours with an average percent of protein about 0.47%, 0.47%, 0.46% and a mass of cell with an average value of 0.77%, 0, 84% and 0.91%. The optimum pH of Rhizopus oryzae growth in the medium of tofu wastewater is about 5 pH. It can be concluded that the wastewater of tofu potentially used as a growth substrate of Rhizopus oryzae. Keywords: Wastewater of Tofu, Single-cell Protein, Rhizopus oryzae.